(untitled) (XXI Century. Spanish Literature and Culture, 2019)
The purpose of this article is to analyze the Esther Tusquets narrative, mainly three issues which are introduced in a symbolic world: maternity, sexuality (homosexual) and the female mindset. This analysis is focused on her novel El mismo mar de todos los veranos (1978). However, the study will be completed with two novels more that create the Trilogía del mar: El amor es un juego solitario (1979) y Varada tras el último naufragio (1980). The objective of this work is to show a complete study from the world of symbols that Tusquets use on this trilogy.